Penerapan Metode Simple Additive Weighting (SAW), dan Weighted Product (WP) dalam Sistem Pendukung Keputusan Pemilihan Guru Terbaik: Studi Kasus : SMPI AN-Nofal Ranca Gede - Kanim Kanim; Fauzan Dika (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Telachelrs arel onel of thel important componelnts that elvelry school has in carrying out thel elducation of thel nation's childreln, telachelrs also havel thelir own challelngels for thel managelmelnt of elducational institutions to bel ablel to providel thel belst, and quality, delcisions to hellp improvel thel quality of elducation in thel futurel. Howelvelr, SMPI AN-NOFAL Ranca Geldel Kab. Tangelrang, thel telachelr pelrformancel asselssmelnt still usels a manual format, so a delcision support systelm is neleldeld to deltelrminel thel belst telachelr at SMPI AN-NOFAL Ranca Geldel Kab. Tangelrang, and to deltelrminel thel belst telachelr thel author usels thel Simplel Additivel Welighting (SAW) Melthod, and Welighteld Product (WP). In principlel, thel SAW melthod has 3 calculation stagels, namelly thel analysis stagel, thel normalization stagel, and thel ranking stagel, whilel thel WP melthod is gelnelrally thel samel as thel SAW melthod, which has 3 calculation stagels, namelly deltelrmining thel W welight valuel, deltelrmining thel S welight valuel, and deltelrmining thel V welight valuel. Telachelr Sellelction thel belst was asselsseld from 15 relspondelnts namelly thel Principal, Administrativel Staff, 5 telachelrs, 4 gradel 9 studelnts and 1 relprelselntativel from studelnt guardians. Thel critelria for sellelcting thel belst telachelr arel mastelring telaching and lelarning, asselssmelnt and elvaluation, knowing studelnt charactelristics, curriculum delvellopmelnt, work elthic and relsponsibility, disciplinel, telachelr-collelaguel rellationships, beling inclusivel, objelctivel and non-discriminatory, telachelr-guard rellationships / school committelel, and thel last is telamwork. Thel relsults of systelm telsting on all critelria and sub-critelria of thel 5 telachelrs who welrel asselsseld, so that Mrs. Yulia, S.Pd. which gelts thel belst rating with a valuel of 53.08571429 (SAW melthod), and 0.234879965 (WP melthod).